2013
DOI: 10.1021/jo401908g
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Copper-Catalyzed Cascade Synthesis of Quinazoline Derivatives

Abstract: The first example of a copper-catalyzed cascade reaction of (2-aminophenyl)methanols with aldehydes using the combination of cerium nitrate hexahydrate and ammonium chloride has been developed, leading to a wide range of 2-substituted quinazolines in moderate to excellent yields. The efficiency of this transformation was demonstrated by compatibility with a wide range of functional groups. Thus, the method represents a convenient and practical strategy for synthesis of 2-substituted quinazoline derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
52
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(54 citation statements)
references
References 42 publications
(19 reference statements)
0
52
0
2
Order By: Relevance
“…[32][33][34][35][36][37][38][39] Stahl et al recently reported that Cu/N-oxyl catalysts promoted hemiaminal oxidation in the aerobic oxidative acylation of amines with primary alcohols. [40] Cu/N-oxyl-catalyzed oxidation of primary amines [41] and secondary amines [42][43][44][45][46] has also been reported so far.However, to the best of our knowledge,there is no precedent for Cu/N-oxyl-catalyzed oxidation of tertiary amines.S ince Cu/N-oxyl-catalyzed alcohol oxidation is believed to proceed in ab ulky closed-shell nitroxyl-Cu adduct, [47][48][49][50] we expected that tertiary amine oxidation would proceed regioselectively at N-methyl-positions due to such steric restriction.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] Stahl et al recently reported that Cu/N-oxyl catalysts promoted hemiaminal oxidation in the aerobic oxidative acylation of amines with primary alcohols. [40] Cu/N-oxyl-catalyzed oxidation of primary amines [41] and secondary amines [42][43][44][45][46] has also been reported so far.However, to the best of our knowledge,there is no precedent for Cu/N-oxyl-catalyzed oxidation of tertiary amines.S ince Cu/N-oxyl-catalyzed alcohol oxidation is believed to proceed in ab ulky closed-shell nitroxyl-Cu adduct, [47][48][49][50] we expected that tertiary amine oxidation would proceed regioselectively at N-methyl-positions due to such steric restriction.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Other methods have also been developed within the past three decades. [30] In the past years, a few methods have described the one-pot multicomponent synthesis of quinazolinones based on catalysts such as NH 2 SO 3 H, [31] thiamine hydrochloride, [32] CuCl, [33] chitosan, [34] nafion-H, [35] Mg-Al-CO 3 , [36] silica gel, [37] and H 6 P 2 W 18 O 6 · 18H 2 O [38] from the reaction of aromatic aldehydes, 2-amino benzimidazole/ 3-amino-1,2,4-triazole, and α-hydroxy C-H acids. Nevertheless, these methods may be restricted to benzaldehyde and have some significant limitations, such as harsh reaction conditions, long reaction time, tedious workup, poor yields, and use of metal-and moisture-sensitive catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Our group have been focusing in the synthesis of quinazolines and a variety of excellent approaches to the quinazolines were developed [10][11][12][13]. At the same time, other groups also developed some novel methods to prepare these quinazoline derivatives [14][15][16][17][18][19][20]. For example, Li [20] developed a KI-catalyzed synthesis of quinazolines from 2-aminobenzoketones, toluene and ammonium salt.…”
Section: Introductionmentioning
confidence: 99%